Institutions for Investment : Establishing a High-Performing Institutional Framework for Foreign Direct Investment - Heilbron, Armando; Whyte, Robert (Washington, DC: World Bank, 2020)
A well-functioning institutional framework can result in higher levels of foreign direct investment. It requires several factors such as a shared strategic vision, solid institutions capable of delivering on their specific mandates and collaborating beyond their walls, and a strong political and financial support for all. The note describes key government functions for investment, suggests a process and principles for creating optimal institutional structures to deliver them, and provides examples. In particular, it examines the role of investment promotion agencies (IPAs) the agency usually tasked with operationalizing government FDI goals as well as the dilemmas that governments face in the context of institutional specialization versus function consolidation.